A MULTIMODAL DISCOURSE ANALYSIS OF SELECTED ADVERTISEMENT OF MALARIA DRUGS - Ayodeji Olowu; Susan Olajoke Akinkurolere (University of Kuningan, 2015)
Abstract: This study identified and analyzed the visual and linguistic components associated with the selected advertisement of malaria drugs. This was with a view to describing the essential communication devices the advertisers of such drugs have employed. Data for the study were drawn from both primary and secondary sources. The primary source for the study comprised 4 purposively selected posters, stickers and drugs literature advertisement on malaria. Analysis of the data followed the framework of Kress and Leeuwen’s Multimodal Discourse Analysis. The results showed that such visual resources as colour, pictures, symbols and icons, gaze and posture enhance the semantic quality of the advertisement. In the whole, the study emphasizes the vitality of visual and linguistic elements as important communication devices in advertising. Keywords: multimodal discourse analysis, visual elements, communication devices, visual grammar.